Zu den Wiedergabemöglichkeiten des deutschen Präfixes ge- im Polnischen - Kroman, Anna (Studia Germanica Posnaniensia, 2018)
In the article the author discusses the problem of contrastive analysis of German deverbal derivates of a construction P (ge-) + SV + Ø with Polish constructions which semantically correspond to them in order to systematize formal types of these equivalents and their semantic analysis.